أثر الفلسفة والمنطق واللغة على أساليب الخطاب الديني عند أمين الخولي - محمد، أسماء الحسيني; نصره، سلوى محمد (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2024)
لقد أخذ الخطاب الديني بوصفه جملة من المقاصد والتعاليم الدينية، حيزا واسعا من الدراسات، حيث عكف المفكرون على قراءته وفهمه وتمحيصه، بغية التطور واللحاق بركب الحضارة، ولكلمة "الخطاب" عامة؛ نوعين من الاستخدام يجب التمييز بينهما، أولهما هو المعنى الشائع بيننا، من استحداث طرق جديدة في مخاطبة المشتغلين بالدين لجمهورهم، كأن يستخدموا أسلوبا لينا أو متعاطفا في وعظهم للناس، أما الثاني فهو المعنى المستمد من تعبيرات الفلسفة وخاصة فلسفة ما بعد الحداثة؛ والذي يلخص الخطاب في منظومة من الأفكار والمفاهيم وطرق التفكير والمواقف تجاه موضوع معين؛ وهو ما يشير إلى كيفية التعامل مع الفكر الديني ذاته، في مقاربته لأساليب الفهم للنص القرآني، لمحاولة بلورة العلاقة بين الخطيب والمتلقي، والتي أكد عليها وأهتم بها بوضوح الشيخ أمين الخولي، لذلك هدف البحث إلى دراسة أهم المبادئ الأساسية والأسس الابستيمولوجية لمنظومة أمين الخولي الفكرية في تجديده لأساليب الخطاب الديني، واستخدم البحث المنهج التحليلي والنقدي. ومن خلال تحليل العلاقة الجوهرية التي جعلها الخولي بين الفلسفة الجمالية والفن القولي اتضح أن: تجديد الخطاب يكون بتجديد البلاغة العربية والتي بدورها محور قضية الإعجاز القرآني، في سبيل خلق أساليب جديدة للخطاب تجمع بين الاستخدامين السابقين له، كما يوصى البحث بعمل العديد من الأبحاث والدراسات حول هذه العلاقة بين البلاغة والفلسفة من أجل تجديد مستنير للخطاب الديني. The word “discourse” in general. There are two types of usage that must be distinguished. The first is the common meaning among us, of developing new ways in which religious professionals address their audiences, such as using a soft or sympathetic style in their preaching to people. As for the second, it is the meaning derived from expressions of philosophy, especially post-modern philosophy. Which summarizes the discourse into a system of ideas, concepts, ways of thinking and attitudes towards a particular topic. This indicates how to deal with religious thought itself, in its approach to the methods of understanding the Qur’anic text, in order to crystallize the relationship between the preacher and the recipient, which Sheikh Amin Al-Khouli clearly emphasized and cared about. Therefore, the research aimed to study the most important basic principles and epistemological foundations of Amin Al-Khouli’s intellectual system. In renewing the methods of religious discourse, the research used the analytical and critical method. By analyzing the fundamental relationship that Al-Kholy made between aesthetic philosophy and verbal art; It turns out that: renewing discourse is through renewing Arabic rhetoric, which in turn is the focus of the issue of the Qur’anic miracle, in order to create new methods of discourse that combine the two previous uses of it. The research also recommends conducting many researches and studies on this relationship between rhetoric and philosophy for the sake of an enlightened renewal of religious discourse.
Keywords: التعاليم الدينية -- الخولي، أمين، ت. 1966 م. -- أسرار البلاغة -- الإعجاز القرآني